Notas sobre la avifauna del Baradero, provincia de Buenos Aires, Argentina - Bodrati, Alejandro; Bodrati, Guillermo; Ferrari, Carlos; Mérida, Emilse; Haene, Eduardo (Nuestras Aves, 1997)
Este trabajo no cuenta con un resumen.